Reflexão sobre as juventudes travestis e transexuais youtubers e a apresentação de suas experiências escolares - Senna, Nanci Modesto Leisnoch Zamboni (2021)
This work proposed to listen and analyze the reports of young trans people on Youtube about their experiences in the school environment. To support the analysis, a bibliographical survey was carried out to discuss the notions of juvenile condition and the juvenile situation, contextualizing the transvestite and transgender youth situation in Brazil, in addition to the discussion of two issues that cross/compose the situation of these youths: cisgenderness and whiteness. The channels were selected by searching for words such as “transvestite”, “trans”, “transsexual” together with the word “school”. The search continued until it reached the number of twelve channels that dealt with the theme of school in some video (there was greater female participation than males with the application of this filter). From these channels, a mapping was made with the profile of these young people, as well as a discussion on the transition process, social name and transmasculin and transfeminine experiences. From the mapping, the two largest channels were selected for further analysis with the discussion of transition at school, strategies for finishing high school and what seems to be expected from the narratives of this Youth (and how this crosses youtubers vídeos)